Analysis of the Results of the Study of the Movement Activity of Football Referees in Proleague and Superleague Games (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article presents the research results aimed at determining the advantages and disadvantages of different categories of football referees by studying and comparing their movement activities during the game. In order to ensure that football referees always have a high level of physical fitness, referees undergo special tests, head referees (either or) undergo tests. This article serves to improve the knowledge of this field for future referees and young scientists.